POSITION OF ETHICS, SCIENCE AND HUMANITY - Sukendar; Aris Prio Agus Santoso (International Journal of Law and Legal Ethics, 2022)
Today, it is very necessary to deepen the philosophy of starting from the smallest things first by examining the parts of the philosophy. Because philosophy can reflect one aspect of the implementation of the principles and beliefs that form the basis of science in solving social problems. Especially if it begins with thinking about the position of ethics, science and humanity which is the basis for socializing. The purpose of this study is to find out how the position of ethics, science and humanity. This research method is carried out with a normative juridical approach with a library approach and a conceptual approach. The results of this study were then analyzed qualitatively. Based on the results of this study, it shows that the position of ethics in social life is as a place to get a critical orientation in dealing with various confusing circumstances of morality. The position of ethics as a science is as an empirical fact embodied in thoughts about good and bad, the position of ethics in humanity is a concept of evaluating the nature of truth or goodness from human social actions as a form of fulfilling all human rights. The position of science as a result of human experience and logic from a systematic and rationalist process of preparation and investigation. While the position of humanity essentially places humans in accordance with their dignity as creatures of God, mutual respect between fellow human beings, to create harmonious interactions, and to realize a just and civilized humanity.